INFORMATION SOCIETY AND THE CRISIS OF TRADITIONAL VALUES: A SOCIO-PHILOSOPHICAL ANALYSIS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The emergence of the information society has significantly transformed social structures, communication patterns, and value systems. While digital technologies have increased access to knowledge and global connectivity, they have also contributed to the erosion and reconfiguration of traditional moral and cultural values. This article examines the socio-philosophical dimensions of the crisis of traditional values in the context of the information society. Using a qualitative conceptual analysis based on secondary literature, the study explores how digitalization, media saturation, and algorithmic governance influence moral relativism, identity fragmentation, and cultural hybridization. The findings suggest that the crisis of values is not a complete disappearance of traditional norms but rather a transformation into pluralistic and contested value systems. The article concludes that ethical digital governance and value-oriented education are necessary to stabilize moral frameworks in the information age.